2017
DOI: 10.4103/1735-1995.200272
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the risk of autism

Abstract: Autism is a developmental disability with age of onset in childhood (under 3 years old), which is characterized by definite impairments in social interactions, abnormalities in speech, and stereotyped pattern of behaviors. Due to the progress of autism in recent decades, a wide range of studies have been done to identify the etiological factors of autism. It has been found that genetic and environmental factors are both involved in autism pathogenesis. Hence, in this review article, a set of environmental fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(74 citation statements)
references
References 176 publications
(241 reference statements)
0
74
0
Order By: Relevance
“…Although diverse genetic (Ramaswami & Geschwind, 2018) and environmental factors (Karimi, Kamali, Mousavi, & Karahmadi, 2017;Modabbernia, Velthorst, & Reichenberg, 2017), as well as their interactions (Abbott, Gumusoglu, Bittle, Beversdorf, & Stevens, 2018;Rijlaarsdam et al, 2017), are thought to contribute to the complex etiology of ASD, ASD's etiology remains poorly understood due to the indirect and small effects of known genetic and environmental factors (Crespi, 2016;Varcin, Alvares, Uljarevi c, & Whitehouse, 2017).…”
mentioning
confidence: 99%
“…Although diverse genetic (Ramaswami & Geschwind, 2018) and environmental factors (Karimi, Kamali, Mousavi, & Karahmadi, 2017;Modabbernia, Velthorst, & Reichenberg, 2017), as well as their interactions (Abbott, Gumusoglu, Bittle, Beversdorf, & Stevens, 2018;Rijlaarsdam et al, 2017), are thought to contribute to the complex etiology of ASD, ASD's etiology remains poorly understood due to the indirect and small effects of known genetic and environmental factors (Crespi, 2016;Varcin, Alvares, Uljarevi c, & Whitehouse, 2017).…”
mentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) reports that, if one identical twin has autism, the other will be affected 36 to 95% of the time and if one non-identical twin has autism, the other twin will be affected about 31% of the time (Ronald et al, 2006;Taniai et al, 2008;Rosenberg et al, 2009;Hallmayer et al, 2011). The lack of complete concordance in ASD studies on identical twins suggests that the disorder may be due to a combination of genetic and environmental factors (Karimi et al, 2017). There are now over 700 genes and over 2,000 copy number variations (CNVs) with potential links to ASD in a professionally curated database for the autism research community called SFARI Gene (Abrahams et al, 2013).…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Similarly, it has been consistently suggested that parental viral infections are associated with the development of autism in their offspring [21][22][23]. Among the infectious diseases, some have been specifically pointed out as contributing to infantile autism when infection occurs during the first trimester of pregnancy [24]. These diseases include rubella [21,[25][26][27], measles, mumps [21,26,27], chicken pox [21,28], influenza [21,23], herpes simplex virus [29], pneumonia, syphilis, varicella zoster [30], and cytomegalovirus [27,[31][32][33].…”
Section: Viral Infectionmentioning
confidence: 99%